Empowerment of Community-Based Information Technology In Irrigation Waste Management Systems For Institutional Strengthening And Promoting Local Circular Economy - M. Yani Syafei; Siti Kurnia Rahayu; Masduki Masduki; Dony Susandi (International Journal Of Community Service, 2025)
Waste problems in the irrigation channels of Bendung Rentang, Majalengka, have disrupted water distribution functions, polluted the environment, and increased public health risks. This community service program aims to empower the local community by strengthening technical capacity, institutional development, and downstreaming of waste processing products based on appropriate technology. A participatory approach was adopted involving 20 members of Komunitas Hujan Keruh in training to operate the Waste Processing System (WPS), establishing a formal waste management group, and providing assistance in marketing products such as Refuse Derived Fuel (RDF), liquid fertilizer, and maggot feed. The results showed a significant increase in participants’ technical knowledge by up to 50%, the formation of a management group with clear standard operating procedures (SOP), and initial trials of product downstreaming to local markets. In conclusion, this program effectively supports a circular economy and is feasible to be replicated in other regions facing similar waste management challenges.